3D Bioprinted In Vitro Metastatic Models via Reconstruction of Tumor Microenvironments. Issue 10 (21st January 2019) - Meng, Fanben; Meyer, Carolyn M.; Joung, Daeha; Vallera, Daniel A.; McAlpine, Michael C.; Panoskaltsis‐Mortari, Angela
Abstract: The development of 3D in vitro models capable of recapitulating native tumor microenvironments could improve the translatability of potential anticancer drugs and treatments. Here, 3D bioprinting techniques are used to build tumor constructs via precise placement of living cells, functional biomaterials, and programmable release capsules. This enables the spatiotemporal control of signaling molecular gradients, thereby dynamically modulating cellular behaviors at a local level. Vascularized tumor models are created to mimic key steps of cancer dissemination (invasion, intravasation, and angiogenesis), based on guided migration of tumor cells and endothelial cells in the context of stromal cells and growth factors. The utility of the metastatic models for drug screening is demonstrated by evaluating the anticancer efficacy of immunotoxins. These 3D vascularized tumor tissues provide a proof‐of‐concept platform to i) fundamentally explore the molecular mechanisms of tumor progression and metastasis, and ii) preclinically identify therapeutic agents and screen anticancer drugs. Abstract : A migration‐inducing, vascularized tumor model platform is created via 3D bioprinting of cells, natural hydrogels, and programmable release capsules. These cell‐laden architectures are designed to recapitulate the primary characteristics of metastasis. The 3D models both physically and chemically reconstruct the tumor microenvironments with high spatiotemporal resolution, offering a tool to bridge the gap between monolayer cell culture and animal models.